Ultrahigh-frequency ultrasound imaging of the dorsum of the hand for aesthetic procedures - Cláudia Borges Fontan; Juliana Borges Fontan; Juliana Paulos de Rezende; Luciana Carmen Zattar; Américo Mota (Sociedade Brasileira de Dermatologia (SBD), 2024)
Hand rejuvenation has become increasingly popular in recent years. Knowledge of the layered anatomy of the hand is crucial for better aesthetic results. In this context, ultra-high-frequency ultrasound (UHFUS) has been used in minimally invasive procedures all over the body, including the hands. To the best of our knowledge, this is the first study to correlate UHFUS evaluation of the dorsal aspect of the hand before, during, and after injectable procedures. We discuss the layered local anatomy of the hand, whose knowledge is crucial for performing safe and effective aesthetic treatments for rejuvenation, and the correlation of the imaging aspects of different procedures and products, as well as its possible complications.